Guardians of Islam religious authority and Muslim communities of late medieval Spain - Miller, Kathryn A. (Columbia University Press, 2008)
"Muslim enclaves within non-Islamic politics are commonly believed to have been beleaguered communities undergoing relentless cultural and religious decline. Cut off from the Islamic world, these Muslim groups, it is assumed, passively yielded to political, social, and economic forces of assimilation and acculturation before finally accepting Christian dogma." "Kathryn A. Miller radically reconceptualizes what she calls the exclave experience of medieval Muslim minorities. By focusing on the legal scholars (faqihs) of fifteenth-century Aragonese Muslim communities and translating little-known and newly discovered texts, she unearths a sustained effort to connect with Muslim coreligionists and preserve practice and belief in the face of Christian influences. Devoted to securing and disseminating Islamic knowledge, these local authorities intervened in Christian courts on behalf of Muslims, provided Arabic translations, and taught and advised other Muslims. Miller follows the activities of the faqihs, their dialogue with Islamic authorities in nearby Muslim politics, their engagement with islamic texts, and their pursuit of traditional ideals of faith. She demonstrates that these local scholars played a critical role as cultural mediators, creating scholarly networks and communal solidarity despite living in an environment dominated by Christianity."--Jacket.